Metabolic Syndrome Among Hypertension Clinic Patients In Bangladesh - Siddique, MA; Sultan, MA; Zaman, MM; Rahim, MA; Rhamar, MA; Azad, SS Al; Parvin, T; Haque, KMHSS (Nepalese Heart Journal, 2004)
The diagnosis of the metabolic syndrome holds promise for enhanced prevention of diabetes and cardiovascular diseases. However, its magnitude in Bangladeshi population is not precisely known.